2022
DOI: 10.21203/rs.3.rs-1292687/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An active zone state switch concentrates and immobilizes voltage-gated Ca2+ channels to promote long-term plasticity

Abstract: A molecularly diverse spectrum of plasticity mechanisms orchestrates brain information processing and storage via positive (“Hebbian”) and negative (“homeostatic”) feedbacks, which, however, mechanistically converge and functionally interact in vivo. The presynaptic scaffold proteins that orchestrate active zone (AZ) function undergo plastic remodeling to regulate release potentiation. Here, voltage-gated Ca2+ channel function and their exact AZ nanoscale distribution steer release, although how they are invol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…This compaction of AZ structure does appear capable of enhancing neurotransmitter release, as a similar compaction has been reported for Ib AZs following a form of adaptive plasticity known as presynaptic homeostatic potentiation (PHP) (Dannhäuser et al, 2022; Goel & Dickman, 2021; Mrestani et al, 2021). Furthermore, an intriguing recent study added an additional layer of regulation of Cac at AZs, where the nanoscale mobility and localization within individual MN-Ib AZs was subject to dynamic regulation at basal and plasticity states (Ghelani et al, 2022). Although these dynamics were not studied at MN-Is AZs, distinctions in Cac mobility and dynamics likely also contribute to the functional differences in tonic vs phasic release sites.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This compaction of AZ structure does appear capable of enhancing neurotransmitter release, as a similar compaction has been reported for Ib AZs following a form of adaptive plasticity known as presynaptic homeostatic potentiation (PHP) (Dannhäuser et al, 2022; Goel & Dickman, 2021; Mrestani et al, 2021). Furthermore, an intriguing recent study added an additional layer of regulation of Cac at AZs, where the nanoscale mobility and localization within individual MN-Ib AZs was subject to dynamic regulation at basal and plasticity states (Ghelani et al, 2022). Although these dynamics were not studied at MN-Is AZs, distinctions in Cac mobility and dynamics likely also contribute to the functional differences in tonic vs phasic release sites.…”
Section: Discussionmentioning
confidence: 99%
“…What mechanism(s) might be responsible for the two-fold higher Ca 2+ influx per action potential at MN-Is release sites over -Ib? While the abundance of Ca V 2 Ca 2+ channels at AZs can increase in the context of presynaptic plasticity (Cao & Tsien, 2010;Ghelani et al, 2022;Goel, Bergeron, et al, 2019;Gratz et al, 2019;Sheng et al, 2012), distinctions in Cac abundance do not appear to explain the differences in Ca 2+ influx at tonic vs phasic release sites. Instead, we consider several possibilities that are not mutually exclusive.…”
Section: Presynaptic Release Properties Of Mn-is Vs -Ibmentioning
confidence: 99%
“…Additionally, RIM interacts stoichiometrically with Ca v 2 (Kaeser et al, 2011;Oh et al, 2021). However, in mammalian central synapses and Drosophila NMJs, loss of RIM and RBP binding to the C-terminal of VGCCs did not reduce channel AZ localization (Schneider et al, 2015;Lübbert et al, 2017;Ghelani et al, 2022). Indeed, several studies reported the lack of RIM and RBP interactions actually promotes channel stability at AZs, opposite to what would be expected for a protein functioning as a VGCC slot interactor (Schneider et al, 2015;Ghelani et al, 2022).…”
Section: The Slot Model For Vgcc Accumulation At Azsmentioning
confidence: 94%
“…The conserved AZ scaffold proteins are attractive candidates for locally mediating slots at the AZ. Drosophila BRP is well situated to be a slot protein, as it binds directly to the Ca v 2 channel and is required for channel accumulation and stabilization at AZs (Fouquet et al, 2009;Ghelani et al, 2022). However, reductions in AZ BRP abundance have no effect on AZ VGCC levels, indicating this protein is likely not a ratelimiting regulator of VGCCs at AZs (Cunningham et al, 2022).…”
Section: The Slot Model For Vgcc Accumulation At Azsmentioning
confidence: 99%
See 1 more Smart Citation